Interactive Meaning in The Photo Series “The Pancasila Values Implementation in Daily Communal Life”: A Visual Grammar - Nugroho, Yusri Estu; Kurniawan, Muhammad Hafiz (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This analysis focuses on the interactive meaning within the visual narratives of the photo series